PEDAGOGICAL NECESSITY OF PREPARING CHILDREN FOR SCHOOL EDUCATION (Universal International Scientific Journal, 2026)
In modern conditions, preparing children for school education remains a pedagogical necessity of today. Because if the child's cognitive processes, achievements and shortcomings are taken into account in time, and modern pedagogical technologies are used, educational work will be effective. This article discusses the need to implement preschool education work forms, educational work methods with the widespread use of didactic games, demonstration-subject activities, and various forms of practical and visual activities of children
Keywords: modern technologies; diagnostics; mental development